Jovens da Renovação Carismática Católica em Belo Horizonte: Mãe da Igreja e Nossa Senhora Rainha - Dias, Vera Maria Passos Wanderley (2010)
The Catholic Charismatic Renewal (RCC) has drawn the attention of social researchers for the great participation of young people not only in prayer groups, which form the basis of RCC, but also in its organization, and the works of the parishes in evangelization. It is increasingly noted the strong presence of youth actively performing, producing and consuming everything that concerns the charismatic communities and attracting other young people to their groups, making use mainly of music and media. This dissertation deals with the Catholic Charismatic Renewal (RCC) described by its young members 15-29 years, belonging to two parishes in the Archdiocese of Belo Horizonte, the Parish of Nossa Senhora Mãe da Igreja (MDI) and Parish of Nossa Senhora Rainha (NSR). By participant observation and thematic stories where the interviewees recount their experiences in the group, we seek to show how the RCC uses music and the mass media, especially television and the Internet to attract young people and turn them into their new media evangelists. The resulting model couple of the reports was constructed using the parameters of sexuality, conversion and lay leadership. The theoretical framework that gives support to this research was designed from the ideas of modernity by Zygmunt Bauman and Georges Balandier as well as studies of Emile Durkheim and Peter Berger on religion. The emphasis on fieldwork enabled socio-anthropological analysis of this option for the youth in modern religion, which joined the RCC shows a return to the sacred and the pursuit of religious belonging for young people in Belo Horizonte